2014
DOI: 10.1039/c4cc06297c
|View full text |Cite
|
Sign up to set email alerts
|

A redox active triad nanorod constructed from covalently interlinked organo-hexametalates

Abstract: A novel nanorod-like inorganic-organic hybrid compound based on polyoxometalate architectures and organic linkers was successfully synthesized, which exhibits reversible reduction-oxidation properties and fascinating photochromism under sunlight illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Despite the simultaneous occurrence of different species in solution, there are limited examples of crystal structures built up by two POM entities. Among these examples, only a few have been reported involving the combination of heteropolyoxomolybdates and isopolyoxomolybdates (Li et al, 2017;Wang et al, 2006;Yu et al, 2011;Mu ¨ller et al, 2000;Zhang et al, 2010) or containing isopolyoxomolybdates and an isopolyoxovanadate (Bayaguud et al, 2014). Fewer examples are reported that include the concomitance of only two isopolyoxomolybdates in a unique crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the simultaneous occurrence of different species in solution, there are limited examples of crystal structures built up by two POM entities. Among these examples, only a few have been reported involving the combination of heteropolyoxomolybdates and isopolyoxomolybdates (Li et al, 2017;Wang et al, 2006;Yu et al, 2011;Mu ¨ller et al, 2000;Zhang et al, 2010) or containing isopolyoxomolybdates and an isopolyoxovanadate (Bayaguud et al, 2014). Fewer examples are reported that include the concomitance of only two isopolyoxomolybdates in a unique crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Furthermore, nanorod triads, in which POMs bis-functionalised with tris(hydroxymethyl)aminomethane ((HOCH2)3CNH2) were used as the linker between two Mo6, have also been reported and displayed redox activity and photochromism. [39][40][41] However, the formation of POM-POM hybrids using this approach is currently mostly limited to hexamolybdates and requires more complex reaction conditions involving the use of additional reagents, such as N,N'-dicyclohexylcarbodiimide (DCC). 42 On the other hand, the formation of triol-functionalised HPOMs can be achieved for a much wider range of POM structure types via a simpler one-pot synthesis involving just mixing of the starting materials under reflux.…”
Section: Introductionmentioning
confidence: 99%
“…The [V 6 O 13 {(OCH 2 ) 3 C-CH 2 OH} 2 ] 2− anion has been used as platform for various post-functionalization [29,30]. The use of -NH 2 as functional group is also convenient for post-functionalization of POMs [17,21,22,31,32], however it is difficult to obtain the [V 6 O 13 {(OCH 2 ) 3 C-NH 2 } 2 ] 2− anion by reacting tris(hydroxymethyl)aminomethane (Tris) with vanadate precursors. Indeed the direct reaction of Tris with decavanadate in dry dimethylacetamide (90 °C overnight) led to the desired compound with a very low yield (< 6%) [21].…”
Section: Introductionmentioning
confidence: 99%